Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep28583
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of 2009 H1N1 influenza viruses during the pandemic correlates with increased viral pathogenicity and transmissibility in the ferret model

Abstract: There is increasing evidence that 2009 pandemic H1N1 influenza viruses have evolved after pandemic onset giving rise to severe epidemics in subsequent waves. However, it still remains unclear which viral determinants might have contributed to disease severity after pandemic initiation. Here, we show that distinct mutations in the 2009 pandemic H1N1 virus genome have occurred with increased frequency after pandemic declaration. Among those, a mutation in the viral hemagglutinin was identified that increases 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…For the 2009S season, we detected a selective sweep at seven amino acid positions throughout the viral genome (in PA (L581M), HA (S203T) (position 202 in Otte et al 34 ), NP (V100I, I373T), NA (V106I, N248D) and NS1 (I123V)) ( Figure 2C, 2D, 2E, 2F and 2I, Supplementary Table 1), which were also described in Otte et al 34 . All of these changes rapidly became predominant in this season and continued to rise in frequency until they were close to fixation in 2010N, suggesting that the new amino acid was present in nearly all sampled isolates in this season.…”
Section: Selective Sweeps In the Evolution Of Ph1n1 Influenza Virusessupporting
confidence: 77%
See 3 more Smart Citations
“…For the 2009S season, we detected a selective sweep at seven amino acid positions throughout the viral genome (in PA (L581M), HA (S203T) (position 202 in Otte et al 34 ), NP (V100I, I373T), NA (V106I, N248D) and NS1 (I123V)) ( Figure 2C, 2D, 2E, 2F and 2I, Supplementary Table 1), which were also described in Otte et al 34 . All of these changes rapidly became predominant in this season and continued to rise in frequency until they were close to fixation in 2010N, suggesting that the new amino acid was present in nearly all sampled isolates in this season.…”
Section: Selective Sweeps In the Evolution Of Ph1n1 Influenza Virusessupporting
confidence: 77%
“…Hereby, particularly the receptor binding properties of HA play an important role. We have also previously shown that HA S203T increases binding to α2,6-linked sialic acids (corresponds to position 202 in Otte et al 34 )…”
Section: Selective Sweeps In the Evolution Of Ph1n1 Influenza Virusesmentioning
confidence: 61%
See 2 more Smart Citations
“…Other tested variant viruses had activation pH values of Ն5.6 and transmitted less efficiently between ferrets, but it is not clear whether poor transmissibility of these viruses was attributed to the higher HA activation pH and/or additional viral traits. Growing evidence indicates that swine can facilitate adaptations of zoonotic influenza viruses to humans, including increased binding to alpha-2,6 SA receptors, increased replication at temperatures found in mammalian respiratory tracts, increased pathogenicity and transmissibility, and decreased HA activation pH (64,65). As virulence and transmissibility are multifactorial traits, additional determinants such as virus morphology, HA-NA balance, and the ability to evade innate immune responses may also be important (66).…”
Section: Discussionmentioning
confidence: 99%